NILAI-NILAI SOSIAL UPACARA ADAT PERKAWINAN SUKU BUGIS WAJO PADA MASYARAKAT DESA SUNGAI JAMBAT KABUPATEN TANJUNG JABUNG TIMUR PROVINSI JAMBI - Ade Rahima; Nadila Mardianti (Aksara: Jurnal Ilmiah Pendidikan Bahasa dan Sastra Indonesia, 2021)
This research aims to describe social values in the traditional marriage ceremony of the Bugis Wajo tribe in Sungai Jambat Village, Desa Tanjung Jabung Timur of Jambi Province. Researchers use qualitative descriptive methods, data collection techniques that are conducted with observation and structured interviews. In this study, data in the form and function of social values were taken from 6 informants, with the provision of samples taken based on the direction of the wind that is the original community of Sungai Jambat Village in Tanjung Jabung Timur. Analysis data is taken from using distributional methods. The results of this study show the form and function of social values in the traditional ceremony of mating Bugis Wajo tribe in the community of Sungai Jambat Village of Tanjung Jabung Timur Jambi Province includes, the form of the social value of aspects of material values, namely clothing, food, boards that can be developed again. The form of the social value of material value that is sandang pangan papan is found in 'cikcing' meaning ring, 'lawasoji' means a small house, 'bongkaliri' glutinous 4 (four) colors. The function of social values as a tool of solidarity in society and can direct the community in thinking and behaving is in the 'badek' sword means used by the bridegroom and serves as a symbol that the man must indeed fight to the woman that he is ready for the household and will protect his wife and children. 'potto naga' means to symbolize the readiness of the bride and groom to enter domestic life in a clean state. In these contacts, pacci leaves, which means pure, convey the meaning of the blessing on four main things. That is the heart: thoughts, ethics, and behavior. Keywords: literature content analysis, social value function